2001
DOI: 10.1128/jcm.39.3.1008-1016.2001
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of the BDProbeTec ET System for Detection of Chlamydia trachomatis and Neisseria gonorrhoeae in Urine Specimens, Female Endocervical Swabs, and Male Urethral Swabs

Abstract: The performance of the Becton Dickinson BDProbe Tec ET System Chlamydia trachomatis and Neisseria gonorrhoeae Amplified DNA Assays (BD Biosciences, Sparks, Md.) was evaluated in a multicenter study. Specimens were collected from 2,109 men and women, with or without symptoms, attending sexually transmitted disease, family planning, and obstetrics and gynecology clinics. Both swab and urine samples were collected, and the results obtained from 4,131 specimens were compared to those from culture and the LCx nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
1
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(189 citation statements)
references
References 32 publications
(24 reference statements)
6
168
1
7
Order By: Relevance
“…LCR and PCR are candidates to replace culture as reference tests, since they are more sensitive and better standardized and have had equivalent specificity in most studies (7,16,22,28,29). An additional advantage of using NAATs is the ability to incorporate a highly sensitive urine test into a two-test patient standard (1), thereby reducing overestimation of cervical test sensitivity and underestimation of cervical and urine test specificities that can result from use of a single-test specimen standard.…”
Section: Discussionmentioning
confidence: 99%
“…LCR and PCR are candidates to replace culture as reference tests, since they are more sensitive and better standardized and have had equivalent specificity in most studies (7,16,22,28,29). An additional advantage of using NAATs is the ability to incorporate a highly sensitive urine test into a two-test patient standard (1), thereby reducing overestimation of cervical test sensitivity and underestimation of cervical and urine test specificities that can result from use of a single-test specimen standard.…”
Section: Discussionmentioning
confidence: 99%
“…The time take to process the two specimen types was very similar, but urine specimens are thought to be more difficult for inexperienced staff to process, 172 and betweencentre variation in estimated sensitivity might be greater for first catch urine specimens (range 50-100%) than for vulval swabs (range 70-100%, with only one centre less than 90%). 173 Published studies performed with women attending STD and family planning clinics have shown that vulvovaginal swabs are acceptable, but the preferred specimen was urine in three studies 167,174,175 and vulvovaginal swabs in one. 176 A small proportion of women in this study, and others, 167 said that they did not take part in screening because they did not want to take a swab specimen themselves.…”
Section: Vulvovaginal Swabs As a Non-invasive Specimen In Womenmentioning
confidence: 99%
“…The BD ProbeTec TM ET System enables the user to characterize and quantify in real-time of up to 564 samples in eight hours [135]. Its usefulness has been shown in clinical setups especially for the detection of Chlamydia trachomatis and Neisseria gonorrhoeae and other pathogens [136][137][138][139][140][141]. The technology is utilized to generate billions of copies of target molecules from a single DNA or RNA template in the one-hour assay time [142].…”
Section: Sda: Strand Displacement Amplificationmentioning
confidence: 99%